Pentingnya Penggunaan Bahasa Indonesia di Lingkungan Kampus sebagai Identitas Nasional terhadap Persatuan - Ajie Rafi Nur Hakim; Nur Afifah April Yani; Yulia Hana Nurlatifah; Maulia Depriya Kembara (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This article was developed for the Indonesian Language Association with national identity and ethnic and scientific insights. Researchers are preoccupied with the time they must spend before completing their course. Indonesian Language Research Results Indonesian language has evolved in the search for a national identity and various ethnicities and students on campus. This means that research must take a number of steps this year to support the Indonesian government in Indonesian Campgrounds. In this article, national identity and various content on Indonesian language sites are selected to ensure membership in the Indonesian Language Campaign